PENGARUH PEMBERIAN PUPUK FOSFAT DAN PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN HASIL KEDELAI (Glycine max L. Merill) - Sumbayak, Ramerson J; Gultom, Rianto R (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2020)
The research is aimed to determine the effect of Phosphate Fertilizer and Organic Fertilizer on the growth and yield of soybeans. This research was conducted in the Experimental Garden of the Faculty of Agriculture, Darma Agung University, Jl.Binjai Km 10.8 Medan, TD Pardede Complex at an altitude of Â± 28m above sea level, which was conducted from July to October 2018. This study used a Randomized Group Design (RBD) ) Factorial in two factors: Phosphate Fertilizer/TSP (P) in 4 levels: P0=0 g / plot, P1=16 g / plot, P2=32 g/plot, and P3=48 g / plot, and Organic fertilizer Mabar Fine Compost in 3 levels:M1=100 g / plot, M2=200 g/plot, and M3=300 g/plot. The results showed that phosphate fertilizer significantly affected the number of productive branches, seed production per plot, and 100 seed dry weight, and had no significant effect on plant height. Mabar Fine Compost significantly affected plant height, number of productive branches, seed production per plot, and 100 seeds dry weight. The interaction of Phosphate Fertilizer and Mabar Fine Compost had no significant effect on all observed variables.